Green Banking Universe and Sustainability Banking Industry in Indonesia: The Influence of Information Technology Governance - Johanna Kezia Putri; Rachel Noverietha Putri; Rossalina Christanti; Albertus Henri Listyanto Nugroho (Universitas Pasundan, 2024)
This study aims to explores the role of green accounting, green innovation, and green technology and the process of accelerating information technology governance in achieving corporate sustainability. As one of the vital sectors, banking has a large share of Indonesia's economy. The empirical gap regarding green accounting practices in Indonesia, especially in the banking sector, will contribute to this research. The processing method used is a regression of top panel data of banking companies listed on the Indonesia Stock Exchange from 2015-2021. The results shows that green technology has a positive effect on banking sustainability in Indonesia. Furthermore, green accounting does not influence the level of banking sustainability, and green innovation negatively influences the level of banking sustainability in Indonesia. The results of this research data analysis are significant findings, considering that the concept and practice of green accounting are increasingly discussed today. This finding can help regulator to more detailed policy derivatives and targeted practice directions in green and sustainability banking are needed. This research provides a new insight about information technology governance to improving implementation green banking to pursue future sustainability banking.